2018
DOI: 10.1634/theoncologist.2017-0493
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Capture-Based Comprehensive Genomic Profiling Identifies Lung Cancer Patients with Well-Characterized Sensitizing Epidermal Growth Factor Receptor Point Mutations That Were Not Detected by Standard of Care Testing

Abstract: This study points out that genomic profiling, as based on hybrid capture next-generation sequencing, can identify lung cancer patients with point mutation in epidermal growth factor receptor (EGFR) missed by standard molecular testing who can likely benefit from anti-EGFR targeted therapy. Beyond the specific findings regarding false-negative point mutation testing for EGFR, this study highlights the need for oncologists and pathologists to be cognizant of the performance characteristics of testing deployed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…The patients with NSCLC with EGFR mutation may benefit from treatment using EGFR TKIs. In this study, the two most common EGFR mutations identified in Chinese patients with NSCLC were exon 19 deletion (36.7%) and L858R mutation (33.4%), which are sensitive to EGFR TKIs, and this was consistent with the findings of the study published with Western people as the main subjects . The exon 20 insertions, which were mostly insensitive to EGFR TKIs , amounted to 3.8% of EGFR mutations, and the most common resistant mutation, T790M , accounted for 5.5% of EGFR mutations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The patients with NSCLC with EGFR mutation may benefit from treatment using EGFR TKIs. In this study, the two most common EGFR mutations identified in Chinese patients with NSCLC were exon 19 deletion (36.7%) and L858R mutation (33.4%), which are sensitive to EGFR TKIs, and this was consistent with the findings of the study published with Western people as the main subjects . The exon 20 insertions, which were mostly insensitive to EGFR TKIs , amounted to 3.8% of EGFR mutations, and the most common resistant mutation, T790M , accounted for 5.5% of EGFR mutations.…”
Section: Discussionsupporting
confidence: 89%
“…For those 5.5% of patients with primary EGFR T790M mutation, which suggests primary resistance, selecting one of the third‐generation EGFR TKIs as first‐line therapy is advisable. NGS is currently the most effective way to detect EGFR gene alterations . By increasing the depth of sequencing, some less common and low‐frequency mutations may be discovered.…”
Section: Discussionmentioning
confidence: 99%
“… 5 The expanded use of NGS found in the present study may have resulted in the increase in the incidence of EGFRex20ins observed between 2011 and 2020, as NGS has an improved ability to identify rare EGFR variants, including EGFRex20ins. 16 , 17 , 18 In a study comparing EGFR detection rates using comprehensive genomic profiling (CGP), an NGS approach, and PCR in 103 cases with confirmed previous EGFR test results, CGP identified 22 patients (21%) with sensitizing EGFR point mutations that were not detected by PCR, including four of seven patients (57%) with EGFR exon 20 mutations. 18 A real-world study using genomic databases to analyze the ability of PCR and NGS to comprehensively identify EGFRex20ins revealed that PCR methods are projected to miss 50% or more of EGFRex20ins, whereas NGS is more likely to detect the full range of EGFRex20ins variants.…”
Section: Discussionmentioning
confidence: 99%
“…However, FISH testing for these genes, unlike RNA-based NGS testing, has been shown to be at risk for false positives [4], and may under-report actionable alterations that could result in denying patients treatment with these highly efficacious TKI inhibitors [5, 6]. Similarly, CGP can detect highly actionable EGFR mutations that predict response to EGFR inhibitors in NSCLC that have been missed by single gene testing [7].…”
Section: Introductionmentioning
confidence: 99%